The Sub-Analysis of HFmrEF and HFrEF Group in CORE-HF Registry : When being Good is Not Enough - Irnizarifka, Irnizarifka; Wasyanto, Trisulo; Arifianto, Habibie; Chau, Titus H. (The Indonesian Heart Association, 2023)
Background : As the prevalence of heart failure (HF) kept rising each year, the burden caused by it also escalating, especially in terms of economic burden. This is urging the physician to quickly tackle the problem. Although HFrEF medications were developing vastly, the outcome of HF in real world still varies. This indicates another approach is still needed to manage HFrEF/HFmrEF comprehensively. This paper is aimed to give an overview of HFrEF and HFmrEF epidemiological data, based on CORE-HF real world data. Methods : The CORE-HF is a single-center, prospective-cohort registry, which enrolls all patients with chronic HF, that were recruited consecutively from the outpatient Sebelas Maret HF Clinic. Both enrollment and follow-up have been performed since January 2018 until December 2022. Variables recorded consists of baseline characteristics, risk factors, subjective indicators, objective diagnostic assessments, therapies, and outcomes (readmission and mortality). Results : The population of this registry was younger (58.7 ± 12.14) compared to other HF registries, with more multi comorbidities. The number of HFrEF patient was higher than HFmrEF (77.7% vs 22.3%), with clinically higher mortality rate (7.2% in the 1st year and 18.2% in the next year). Although triple therapy initiation and uptitration were excellent in number, the mortality rate during second year of follow-up was higher than other registries. We found non-compliant behavior to be responsible for those results. Conclusion : Based on CORE-HF sub-analysis of the HFrEF and HFmrEF groups, adherence to HF guidelines is the main but not the only key leading to lower mortality and rehospitalization. Our data provide satisfying low hard outcomes, but solving the non-compliance behavior and optimizing the non-pharmacological approach should be done comprehensively by the HF team.This article has a related Erratum.